Tailoring grain and intermetallic of as-extruded Al-La-Mg-Fe alloy: Towards a balance of mechanical properties at room and elevated temperatures - Tao Ban; Zhi Wang; Liejun Li; Zhuoran Li; Jixiang Gao; Xinkui Zhang; Zhengwu Peng (Journal of Materials Research and Technology)
This study successfully develops a novel Al-La-Mg-Fe alloy with a balance of room-temperature and high-temperature mechanical properties through precise control of grain structure and intermetallics via hot extrusion process. The as-extruded Al-La-Mg-Fe alloys achieve enhanced room-temperature mechanical properties (UTS: 293 ± 13 MPa, El: 6.6 ± 0.3 %) coupled with remarkable high-temperature strength-ductility synergy (UTS: 158 ± 5 MPa, El: 24.7 ± 3.0 %). The enhanced room-temperature strength-ductility balance originates from the synergistic effects of refined grains, finely dispersed intermetallics, and narrowed intermetallic-free zones, which collectively enhance dislocation motion resistance and promote dislocation accumulation. Moreover, the combined influence of high volume fraction of coarsening-resistant Al11La3 and Al13Fe4 intermetallics and optimized grain boundary density effectively mitigates the detrimental effects of enhanced atomic diffusion and accelerated grain boundary migration at elevated temperatures, resulting in a 54 % strength retention at 300 °C and demonstrating exceptional high-temperature mechanical performance. Additionally, the crack-buffering zones and blunting mechanisms during high-temperature tensile deformation significantly enhance the plasticity of the alloy. These findings establish fundamental principles for the coordinated optimization of grain size and intermetallics in developing heat-resistant aluminum alloys.